Long-Term High-Altitude Hypoxia and Alpha Adrenoceptor-Dependent Pulmonary Arterial Contractions in Fetal and Adult Sheep - Moretta, Dafne; Papamatheakis, Demosthenes G.; Morris, Daniel P.; Giri, Paresh C.; Blood, Quintin; Murray, Samuel; Ramzy, Marian; Romero, Monica; Vemulakonda, Srilakshmi; Lauw, Sidney; Longo, Lawrence D.; Zhang, Lubo; et al. (Frontiers in Physiology, 2019)
Autonomic innervation of the pulmonary vasculature triggers vasomotor contractility predominately through activation of alpha-adrenergic receptors (α-AR) in the fetal circulation. Long term hypoxia (LTH) modulates pulmonary vasoconstriction potentially through up-regulation of α1-AR in the vasculature. Our study aimed to elucidate the role of α-AR in phenylephrine (PE)-induced pulmonary vascular contractility, comparing the effects of LTH in the fetal and adult periods on α-AR subtypes and PE-mediated Ca2+ responses and contractions. To address this, we performed wire myography, Ca2+ imaging and mRNA analysis of pulmonary arteries from ewes and fetuses exposed to LTH or normoxia. Postnatal maturation depressed PE-mediated contractile responses. α2-AR activation contracted fetal vessels; however, this was suppressed by LTH. α1A- and α1B-AR subtypes contributed to arterial contractions in all groups. The α1D-AR was also important to contractility in fetal normoxic vessels and LTH mitigated its function. Postnatal maturity increased the number of myocytes with PE triggered Ca2+ responses while LTH decreased the percentage of fetal myocytes reacting to PE. The difference between myocyte Ca2+ responsiveness and vessel contractility suggests that fetal arteries are sensitized to changes in Ca2+. The results illustrate that α-adrenergic signaling and vascular function change during development and that LTH modifies adrenergic signaling. These adaptations may represent components in the etiology of pulmonary vascular disease and foretell the therapeutic potential of adrenergic receptor antagonists in the treatment of pulmonary hypertension.